A low-cost virtual coach for 2D video-based compensation assessment of upper extremity rehabilitation exercises - Ana Rita Cóias; Min Hun Lee; Alexandre Bernardino (Journal of NeuroEngineering and Rehabilitation, 2022)
Abstract Background The increasing demands concerning stroke rehabilitation and in-home exercise promotion grew the need for affordable and accessible assistive systems to promote patients’ compliance in therapy. These assistive systems require quantitative methods to assess patients’ quality of movement and provide feedback on their performance. However, state-of-the-art quantitative assessment approaches require expensive motion-capture devices, which might be a barrier to the development of low-cost systems. Methods In this work, we develop a low-cost virtual coach (VC) that requires only a laptop with a webcam to monitor three upper extremity rehabilitation exercises and provide real-time visual and audio feedback on compensatory motion patterns exclusively from image 2D positional data analysis. To assess compensation patterns quantitatively, we propose a Rule-based (RB) and a Neural Network (NN) based approaches. Using the dataset of 15 post-stroke patients, we evaluated these methods with Leave-One-Subject-Out (LOSO) and Leave-One-Exercise-Out (LOEO) cross-validation and the $$F_1$$ F 1 score that measures the accuracy (geometric mean of precision and recall) of a model to assess compensation motions. In addition, we conducted a pilot study with seven volunteers to evaluate system performance and usability. Results For exercise 1, the RB approach assessed four compensation patterns with a $$F_1$$ F 1 score of $$76.69 %$$ 76.69 % . For exercises 2 and 3, the NN-based approach achieved a $$F_1$$ F 1 score of $$72.56 %$$ 72.56 % and $$79.87 %$$ 79.87 % , respectively. Concerning the user study, they found that the system is enjoyable (hedonic value of 4.54/5) and relevant (utilitarian value of 4.86/5) for rehabilitation administration. Additionally, volunteers’ enjoyment and interest (Hedonic value perception) were correlated with their perceived VC performance ( $$ρ = 0.53$$ ρ = 0.53 ). Conclusions The VC performs analysis on 2D videos from a built-in webcam of a laptop and accurately identifies compensatory movement patterns to provide corrective feedback. In addition, we discuss some findings concerning system performance and usability.